Evaluasi pengembangan agribisnis kakao di Kabupaten Kaimana - AITUARAUW, Muhammad Nasir ([Yogyakarta] : Universitas Gadjah Mada, 2010)
One of the plantation commodity that is very important in contributing to national income is cocoa. This study aims to determine the factors that influence the production of cocoa after the legacy of PT. Mulia Jaya Adi and analyze the feasibility of farmers cultivated cocoa farming heritage post-PT. Mulia Jaya Adi on cocoa production. This research was conducted in Kaimana District as the center of cocoa cultivation in Manokwari, or about 60% of the total land area of cocoa. Data collection was done in two ways, namely: using primary and secondary data. Data collection techniques using three different ways, namely observation, interview and record keeping. Results showed that (1) Production of cocoa farming, influenced by land area, farmers' age, educational level, farming experience and manpower. (2) cocoa farming on the island of Adi Kaimana feasible to cultivated by farmers. (3) cocoa farming on the island of Adi Kaimana profitable.